Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1063/1.3691224
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of electron conduction in contact resistive random access memory devices as random telegraph noise

Abstract: The intense development and study of resistive random access memory (RRAM) devices has opened a new era in semiconductor memory manufacturing. Resistive switching and carrier conduction inside RRAM films have become critical issues in recent years. Electron trapping/ detrapping behavior is observed and investigated in the proposed contact resistive random access memory (CR-RAM) cell. Through the fitting of the space charge limiting current (SCLC) model, and analysis in terms of the random telegraph noise (RTN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…The bulk-limited mechanism depends on the electric characteristics of dielectric material itself and can be divided into different modes, including FowlerNordheim tunneling, Pool-Frenkel model (trap-assisted thermionic emission), and trap-assisted space-charge-limited current (trap-assisted SCLC). 25 For our device with 0.4 mm diameter, its I-V curve is fitted with all aforementioned models, and the best fitting is shown in Fig. 3(d), in which the I-V curve is in a double natural logarithmic plot.…”
mentioning
confidence: 99%
“…The bulk-limited mechanism depends on the electric characteristics of dielectric material itself and can be divided into different modes, including FowlerNordheim tunneling, Pool-Frenkel model (trap-assisted thermionic emission), and trap-assisted space-charge-limited current (trap-assisted SCLC). 25 For our device with 0.4 mm diameter, its I-V curve is fitted with all aforementioned models, and the best fitting is shown in Fig. 3(d), in which the I-V curve is in a double natural logarithmic plot.…”
mentioning
confidence: 99%
“…In [17], an explanation for why RTN affects HRS more than LRS is attributed to the difference in V o density in the CF. Also, in [17,20], re-writing the memory cell is shown to permanently change the RTN behavior, in some cases, RTN behavior can disappear [19].…”
Section: Introductionmentioning
confidence: 97%
“…RTN studies conducted specifically on ReRAM devices [8,[17][18][19][20] also characterize T e and T c . In [18] it is observed that V o 's near the conductive filament, which is composed of V o 's, is a major factor to cause RTN and retention loss.…”
Section: Introductionmentioning
confidence: 99%
“…However, before the commercial exploitation of this emerging technology, two major concerns need to be solved: device endurance and switching variability. In order to determine the reliability and stochastic variability of the memory performance, a better understanding of random telegraph noise (RTN) in RRAM cells is required, as it can cause severe operation or read errors [2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%